Development of Sme Based Opinion Leadership Model in Indonesia - Chairunnisya Chairunnisya (Jurnal Indonesia Sosial Sains, 2025)
The decline in sales is one of the impacts of the Covid 19 pandemic on SME, and another impact is a decrease in production and a decrease in the total income of SME. Opinion leadership can solve consumer behavior in Indonesian society, especially after the Covid 19 pandemic. This research aim to determine the SME-based opinion leadership model in Indonesia during the Covid 19 pandemic and to analyze the relationship between opinion leadership and consumer behavior in SMEs during the Covid 19 pandemic. This research is quantitative through an online survey, the data analysis and hypothesis testing method use the Structural Equation Model - Partial Least Square (SEM-PLS). It was found that opinion leadership significantly affects consumer behavior in SMEs in Indonesia with four characteristics, professional, innovative, involved, and socialized. This research can be used for SME to start digitalizing by having a social media account to share information alongside the efforts of opinion leaders. Opinion leaders have a specialty depending on their capability, so they can promote SME products that match their personality. In addition, having many followers can make opinion leaders lead a community.